Mobile near-field terahertz communications for 6G and 7G networks: Research challenges - Petrov, Vitaly; Bodet, Duschia; Singh, Arjun (Frontiers in Communications and Networks, 2023)
Following the current development of the wireless technology landscape, and with respect to the constant growth in user demands, it is inevitable that next-generation mobile wireless networks will use new frequency bands located in the sub-terahertz and terahertz (THz) spectrum to complement the existing microwave and millimeter wave (mmWave) channels. The feasibility of point-to-point stationary THz communication links has already been experimentally demonstrated. To build upon this breakthrough, one of the pressing research targets is making THz communication systems truly mobile. Achieving this target is especially complicated because mobile THz wireless systems (including WLANs and even cellular access) will often operate in the near-field due to the very large (even though physically small) electrical size of the high-gain antenna systems required for making high-rate communication links feasible at such frequencies. This perspective article presents several key prospective research challenges envisioned on the way to designing efficient mobile near-field THz wireless access as a part of 6G and 7G wireless landscapes.